SIŁY SPOŁECZNE W WOJEWÓDZTWIE POZNAŃSKIM - Znaniecki, Florian (Wydział Prawa i Administracji UAM, 2002)
The text is F. Znaniecki’s so far unpublished project submitted to the Local Government Department of the Provincial Council in Poznań on the 3rd February 1934. The text, opened with the author’s introduction, bears out Znaniecki’s interest in the region and its social processes.
POLITICAL POWERS IN THE PROVINCE OF POZNAŃ